Guest

Hi, Can you help me in solving a^(logb-logc)x b^(logc-loga)x c^(loga-logb)=? Thanks and regards, AN

Hi,

Can you help me in solving

a^(logb-logc)x b^(logc-loga)x c^(loga-logb)=?

Thanks and regards,
AN

Grade:9

2 Answers

mycroft holmes
272 Points
11 years ago

mahabahu indian
35 Points
11 years ago

let required value=k

then take log at both side

L.H.S will be 0

that means logk=0

so k=1

 

 

plz bhayia like my reply

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free